History of Islamic philosophy - Arif Ali Khan (New Delhi : Pentagon, 2007)
"Ever since the growth of Islam as a religious and political movement, Muslim thinkers have sought to understand the theoretical aspects of their faith by using philosophical concepts. Leaman outlines this history and demonstrates that, although the development of Islamic philosophy is closely linked with Islam itself, its form is not essentially connected to religion, and its leading ideas and arguments are of general philosophical significance. The author illustrates the importance of Islamic thought within philosophy through the use of many modern examples. He describes and contrasts the three main movements in Islamic philosophy - Peripatetic, Sufi and Illuminationist - and examines the Persian as well as the Arabic traditions. Coverage is given to key aspects of Islamic philosophy, including epistemology, ontology, politics, ethics, and philosophy of language, providing readers with a full and rounded view of the discipline.".
"This book will be for second-year undergraduates and above in philosophy, religious studies and Islamic studies and also to the lay reader concerned with philosophical and religious issues."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Islamic philosophy